Factors associated with ocular surface disease and severity in adults with atopic dermatitis: a nationwide survey. (15th December 2021) - Rønnstad, A.T.M.; Hansen, P.M.; Halling, A.S.; Egeberg, A.; Kolko, M.; Heegaard, S.; Thyssen, J.P.
Abstract: Background: Ocular surface diseases (OSDs), including conjunctivitis and blepharitis, are common in atopic dermatitis (AD) patients, but the magnitude and patient characteristics are unclear. Objectives: To examine the prevalence of OSDs in adults with AD and identify patient characteristics and risk factors. Methods: We designed a cross‐sectional questionnaire‐based survey and sent it via a secure public mail to all adult Danes with a hospital diagnosis of AD (ICD‐10 code L20.x) registered in the National Patient Register ( n = 16 718) between 2000 and 2019 and 7044 (42%) participated. Primary outcomes were OSDs and severity according to Ocular Surface Disease Index (OSDI). Adjusted odds ratios (aOR) were calculated with 95% confidence intervals (CIs) using logistic regression models. Results: Respondents were mostly females and middle‐aged (67.4%, mean [SD] age, 39.0 [15.5] years). Based on Patient‐Oriented SCORing Atopic Dermatitis 49% had mild AD, 35% moderate, 10% severe and in 6% AD was inactive; 44.3% reported physician‐diagnosed asthma bronchiale and 55.8% rhinitis. The lifetime prevalence of OSDs was 66.6% for conjunctivitis, 63.5% for hordeolum, 11.0% for blepharitis, 9.7% for keratitis, 2.0% for pterygium, 1.5% for symblepharon, 1.1% for keratoconus and 12.7% reported current conjunctivitis. Factors associated with lifetime occurrence of conjunctivitis included mild, moderate, and severe AD (aOR = 1.48 [95% CI, 1.02–2.14], aOR = 1.73 [95% CI, 1.19–2.53], aOR = 2.17 [95% CI, 1.42–3.21]), asthma bronchiale and rhinitis (aOR = 1.76 [95% CI, 1.49–2.07]), childhood‐onset of AD (aOR = 1.34 [95% CI, 1.16–1.56]) and systemic AD treatment (aOR = 1.27 [95% CI, 1.08–1.50]). Use of soft and hard contact lenses (aOR = 2.15 [95% CI, 1.65–2.80], aOR = 3.35 [95% CI, 1.62–6.92]) were associated with lifetime occurrence of keratitis. Moderate and severe AD, asthma bronchiale and rhinitis were also associated with a higher OSDI level. Conclusions: This study identified important patient factors associated with OSDs. Clinicians should be attentive of ocular signs and symptoms in AD patients and ask about these.